Activation of LFA-1 through a Ca2(+)-dependent epitope stimulates lymphocyte adhesion (The Rockefeller University Press, 1991)
The leukocyte function-associated molecule-1 (LFA-1) plays a key role in cell adhesion processes between cells of the immune system. We investigated the mechanism that may regulate LFA-1-ligand interactions, which result in cell-cell adhesion. To this end we employed an intriguing anti-LFA-1 alpha mAb (NKI-L16), capable of inducing rather than inhibiting cell adhesion. Aggregation induced by NKI-L16 or Fab fragments thereof is not the result of signals transmitted through LFA- 1. The antibody was found to recognize a unique Ca2(+)-dependent activation epitope of LFA-1, which is essentially absent on resting lymphocytes, but becomes induced upon in vitro culture. Expression of this epitope correlates well with the capacity of cells to rapidly aggregate upon stimulation by PMA or through the TCR/CD3 complex, indicating that expression of the NKI-L16 epitope is essential for LFA- 1 to mediate adhesion. However, expression of the NKI-L16 epitope in itself is not sufficient for cell binding since cloned T lymphocytes express the NKI-L16 epitope constitutively at high levels, but do not aggregate spontaneously. Based on these observations we propose the existence of three distinct forms of LFA-1: (a) an inactive form, which does not, or only partially exposes the NKI-L16 epitope, found on resting cells; (b) an intermediate, NKI-L16+ form, expressed by mature or previously activated cells; and (c) an active (NKI-L16+) form of LFA- 1, capable of high affinity ligand binding, obtained after specific triggering of a lymphocyte through the TCR/CD3 complex, by PMA, or by binding of NKI-L16 antibodies.